Effects of matrix support implementation on the community mental health network in a medium-sized Brazilian municipality: a repeated cross-sectional study - Carlos Alberto dos Santos Treichel; Maria Giovana Borges Saidel; Ana Laura Salomé Lourencetti; Sulamita Gonzaga Silva Amorim; Lívia Penteado Pinheiro; Rosana Teresa Onocko-Campos (Cadernos de Saúde Pública)
Abstract: Given the centrality of comprehensive care and network organization as key outcomes of matrix support, this study aims to examine changes in the operation of the community mental health network in Itatiba, São Paulo State, Brazil, after the implementation of matrix support, focusing on three main components: (i) users’ profile; (ii) identification of available therapeutic interventions; and (iii) analysis of the clinical care received by participants across the studied services. This is a repeated cross-sectional, document-based descriptive study with two measurement points (T0 and T1). Data for T0 were collected between May and July 2019, and for T1 between November and December 2021. A total of 1,958 records were analyzed at T0 and 1,431 at T1, using descriptive statistical analysis to estimate absolute and relative frequencies for each variable. The findings indicate substantial changes in referral patterns following matrix support implementation, with a decrease in spontaneous demand and a greater role of primary care in coordinating access to specialized mental health services. Improvements were also observed in clinical care, with increased attention to vital signs measurement, anamnesis, physical exams, and documentation of smoking, alcohol, and psychoactive substance use. These results suggest that matrix support contributed to a more structured and effective mental health network, enhancing integration between care levels and promoting more comprehensive and accessible care.